Hybrid project management for sociotechnical digital transformation context - Monteiro Cavalieri Barbosa, Adriane; Pego Saisse, Manoel Carlos (Brazilian Journal of Operations & Production Management, 2019)
Goal: The path to implement Digital Transformation (DT) in modern industries is far from clear, particularly in Brazil. From the point of view of operations management, authors developed a Conceptual Framework (CF) to support DT implementation in Discrete Manufacturing Industries (DMI). The CF applies knowledge management, hybrid project management (HPM) and Sociotechnical values to implement DT, using New Product Development (NPD) as a ground. The work aims to depict the HPM approach of this CF. Design / Methodology / Approach: this is a qualitative research based on a systematic literature review carried out over a period of five years. It was performed in the Web of Science database, applying PRISMA flowchart, to evaluate which project management models, addressed in the literature, are more suitable for DT implementation projects in light of sociotechnical and innovation-shared-values approach. Results: A Hybrid “Stage-Gate – Agile - Design Thinking” project management model to support DT implementation in DMI. This is a preliminary proposal that can be explored in future empirical research. Limitations of the investigation: Some quality papers may have been left out due to the research methodology. Practical implications: The CF can be applied by professionals to support Digital Transformation while incorporating sociotechnical values and reducing the excessive technological bias in NPD projects. Originality/Value: The authors propose a new Digital Transformation (DT) approach, named Sociotechnical Digital Transformation (SDT) and an HPM to support DT in light of a Sociotechnical approach.